(3efJbjGJ TYQjIs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg hef bhd Gdabjg GdWhjQ GdbjQhGfi jPcQ eG CUGH Cgd LeGd ai TbGbge, hTbge GdYUG, hYah ehdGfG Yfge HYO Pdc s
(3BNQgG (B:s
(3aEPG geG GLJeYG GdfaS eQI HdZ ef GdYdjGA cd ecGf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B32 - 126 - (3U(B92 -131s
(3HgG fXGe GdJYbjHIs
(3hgj Vef eLehYI (B32 - 92 (3, (B126 - 131 s
(3JHUQI GdYfhGf (B:s
(3GNJjGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdCOHs